Martha Stewart's favorite crafts for kids : 175 projects for kids of all ages to create, build, design, explore, and share - Stewart, Martha; Schlechter, Annie; Martha Stewart Living Omnimedia (New York : Potter Craft, 2013)
A guide for crafty kids and their parents mixes a family friendly design with a treasure trove of creative and educational projects that parents and their kids, aged three to twelve, can create together.
Create a few characters -- Build a little world -- Make your own fun -- Design it yourself -- Experiment and explore -- Keep it together -- Give something handmade
Includes index.
Keywords: Handicraft -- Juvenile literature